Derivation of Century-Based Wave Climate and Extreme Wave Analysis Along Turkish Coasts - Turgut, Ahmet Rıza; Özbahçeci, Bergüzar (Izmir Institute of Technology, 2019)
Reliable and long-term wave data are essential for the design of almost all coastal and marine structures. In this study, the wave climate along the Turkish coasts was derived based on a century long data of European Centre for Medium-Range Weather Forecasts. For this purpose, firstly, the data set was calibrated and verified by using satellite and in-situ measurements. Then the design waves corresponding to different return periods were determined by extreme statistics. Therefore, a new and reliable design wave height data along the Turkish coasts have been provided for the designers and applicants. Results were compared with Wind and Deep Water Wave Atlas Along the Turkish Coasts (Ozhan and Abdalla, 2002). The comparison results indicate that the design wave heights provided by the Atlas are higher than the current study, especially in the Aegean Sea. Moreover, the effect of theoretical distribution function and the data number were investigated on the design wave height. Design wave heights were recalculated by best fitting distribution function and it was shown that distribution function may affect the design wave height. It was also concluded that when the wave data used in extreme value analysis was less than 30 years, the error increased in the estimation of the design wave height with both 50 and 100 years return periods. Besides, by using calibrated and the verified century-long wave climate data it was shown that there was an increasing trend in the annual mean and maximum wave heights along the Turkish coasts.

Deniz yapılarının güvenli ve ekonomik tasarımı, en önemli yüklerden olan dalga tasarım verilerinin doğru belirlenmesine bağlıdır. Bunun için uzun dönemli dalga iklimi çalışması gereklidir. Bu çalışmada Avrupa Orta Ölçekli Hava Tahmin Ajansı (ECMWF) tarafından üretilen 110 yıllık dalga verisi uydu verileri ve yerinde ölçüm verileriyle kalibre edilmiş ve doğrulaması yapılmış ve Türkiye kıyıları için kullanılabilir hale getirilmiştir. Böylece ilk kez asırlık dalga iklimi ortaya çıkarılmıştır. Bu çalışma ile aynı zamanda ülkemizin Karadeniz, Akdeniz ve Ege kıyılarını temsil edecek noktalarda çeşitli yinelenme dönemine sahip ekstrem dalgalar belirlenmiş, tasarımcı ve uygulamacılar için tasarım dalgasının seçilmesinde güncellenmiş ve güvenilir bir kaynak sağlanmıştır. Sonuçlar NATO TU Waves Projesi kapsamında Özhan ve Abdalla (2002) tarafından hazırlanan Rüzgâr ve Derin Deniz Dalga Atlası ile karşılaştırılmış, bu çalışmada bulunan tasarım dalgalarının özellikle Ege Denizinde daha düşük olduğu görülmüştür. Çalışma kapsamında, kısa dönemli veriden dolayı şimdiye kadar ekstrem değerleri elde etmek için kullanılan en büyük değer istatistiği yönteminin sonuca etkisi araştırılmıştır. Dağılım modeli ve veri sayısının tasarım değerlerini etkilediği görülmüştür. Bu çalışma ile Türkiye kıyılarında ilk kez yüzyılı aşan bir süreçte ve bütünleşik olarak ortalama ve en yüksek dalga yüksekliğinde bir değişim eğiliminin olup olmadığı incelenmiştir. Sonuçlar kıyılarımızın önemli bir kısmında yıllık maksimum ve ortalama dalgada artma eğilimi olduğunu göstermiştir.
Türkiye Kıyıları için Dalga İkliminin Elde Edilmesi ve Ekstrem Dalga Analizi
Thesis (Master)--Izmir Institute of Technology, Civil Engineering, Izmir, 2019
Includes bibliographical references (leaves: 66-69)
Text in English; Abstract: Turkish and English
Keywords: Wind waves; Wave climatology; Sea coasts; Extremal order statistics; Turkish coasts; Extreme wave analysis